Implementasi Kebijakan Penanganan Perlintasan Sebidang Tidak Terdaftar dalam Rangka Keselamatan Kereta Api dan Masyarakat di Sumatera Barat - Syafriandi Syafriandi; Aldri Frinaldi (Journal of Education on Social Science (JESS), 2026)
This study analyzes the implementation of policies for handling unregistered level crossings to improve railway and public safety in West Sumatra. The issue is significant because unregistered level crossings remain dominant, with 189 of 310 active crossings, and accident data from 2021–2025 show continuing safety risks involving road users, fatalities, serious injuries, and minor injuries. This research employed a descriptive qualitative approach using grounded theory analysis. Data were collected through in-depth interviews, field observations, and documentation involving 37 informants from railway regulators, operators, local governments, law enforcement agencies, field officers, and road users. Data analysis was conducted through open coding, axial coding, and selective coding. The findings indicate that policy implementation is influenced by institutional authority, cross-sector coordination, resource limitations, technical risks at crossings, public access needs, road user behavior, and community acceptance. The study found that handling unregistered level crossings cannot rely solely on physical closure, as many crossings function as daily access routes for communities. Therefore, effective policy implementation requires risk-based data collection, clarification of authority, inter-agency coordination, improvement of safety facilities, continuous public education, law enforcement, and provision of alternative access routes. The core finding shows that the handling of unregistered level crossings must be based on institutional synergy, safety considerations, and community acceptance. This study contributes to public administration and transport safety governance by emphasizing a collaborative, data-driven, and socially responsive model for managing unregistered level crossings.